Stalin and the bomb : the Soviet Union and atomic energy, 1939-1956 - Holloway, David, 1943- (New Haven : Yale University Press, 1994)
In engrossing detail, David Holloway tells us how Stalin launched a crash atomic program only after the Americans bombed Hiroshima and showed that the bomb could be built; how the information handed over to the Soviets by Klaus Fuchs helped in the creation of their bomb; how the scientific intelligentsia, which included such men as Andrei Sakharov, interacted with the police apparatus headed by the suspicious and menacing Lavrentii Beria; what steps Stalin took to counter U.S. atomic diplomacy; how the nuclear project saved Soviet physics and enabled it to survive as an island of intellectual autonomy in a totalitarian society; and what happened when, after Stalin's death, Soviet scientists argued that a nuclear war might extinguish all life on earth.
This magisterial history throws light on Soviet policy at the height of the Cold War, illuminates a central but hitherto secret element of the Stalinist system, and puts into perspective the tragic legacy of this program - today environmental damage, a network of secret cities, and a huge stockpile of unwanted weapons.
1. Ioffe's Institute -- 2. Nuclear Prehistory -- 3. Reacting to Fission -- 4. Making a Decision -- 5. Getting Started -- 6. Hiroshima -- 7. The Post-Hiroshima Project -- 8. The Premises of Policy -- 9. The Atomic Industry -- 10. The Atomic Bomb -- 11. War and the Atomic Bomb -- 12. The War of Nerves -- 13. Dangerous Relations -- 14. The Hydrogen Bomb -- 15. After Stalin -- 16. The Atom and Peace.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Nuclear weapons -- Government policy -- Soviet Union -- History; Nuclear energy -- Research -- Soviet Union -- History; Science and state -- Soviet Union -- History; Soviet Union -- Foreign relations; Armes nucléaires -- Politique gouvernementale -- URSS -- Histoire; Énergie nucléaire -- Recherche -- URSS -- Histoire; Politique scientifique et technique -- URSS -- Histoire; URSS -- Relations extérieures.; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; POLITICAL SCIENCE -- General; Diplomatic relations; Nuclear energy -- Research; Nuclear weapons -- Government policy; Science and state; Soviet Union; Atomare Rüstung; Kernenergie; Kernwaffe; Sowjetunion; Bewapeningswedloop; Kernwapens; Wapenproductie; Electronic books; History